How does the search for knowledge drive firms' eco-innovation? Evidence from the wine industry. Issue 3 (3rd April 2017) - Muscio, Alessandro; Nardone, Gianluca; Stasi, Antonio
Abstract: The importance of eco-innovations to food manufacturing has risen exponentially in recent years. In this paper we investigate the drivers of different types of eco-innovation in the Italian wine industry, a particularly relevant sector both in terms of its economic performance and its use of natural resources. We focus on the internal knowledge sourcing of firms and on the 'breadth' and 'depth' of their engagement with external agents when performing eco-innovation activity. We test our research hypotheses in the context of cleaner processes, end-of-pipe technologies and the use of organic input factors. The empirical evidence is based on a questionnaire survey administered to 334 Italian wine producers. The econometric exercise provides mixed results: both internal R&D and engagement with external agents have a significant effect on eco-innovations depending on the type of eco-innovation taken into account. Moreover, we find a non-linear relationship between external knowledge sourcing and eco-innovation activity.